2011
DOI: 10.4049/jimmunol.1002955
|View full text |Cite
|
Sign up to set email alerts
|

Memory CD4 T Cells That Express CXCR5 Provide Accelerated Help to B Cells

Abstract: CD4 T cell help for B cells is critical for effective Ab responses. Although many of the molecules involved in helper functions of naive CD4 T cells have been characterized, much less is known about the helper capabilities of memory CD4 T cells, an important consideration for the design of vaccines that aim to prime protective memory CD4 T cells. In this study, we demonstrate that memory CD4 T cells enable B cells to expand more rapidly and class switch earlier than do primary responding CD4 T cells. This acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 46 publications
6
112
0
Order By: Relevance
“…found that the number of antigen‐specific memory cells that expressed Tfh markers declined over time, suggesting that Tfh cells fail to differentiate into long‐lived memory cells 57. However, we and others have shown that both mouse and human CXCR5+ memory CD4 T‐cells provide rapid assistance to B‐cells upon reactivation 61, 62, 63, 64, 65, 66, 67, 68, 69. Importantly, Alexander et al .…”
Section: Memory Cd4 T‐cells Are Found Throughout the Bodymentioning
confidence: 73%
“…found that the number of antigen‐specific memory cells that expressed Tfh markers declined over time, suggesting that Tfh cells fail to differentiate into long‐lived memory cells 57. However, we and others have shown that both mouse and human CXCR5+ memory CD4 T‐cells provide rapid assistance to B‐cells upon reactivation 61, 62, 63, 64, 65, 66, 67, 68, 69. Importantly, Alexander et al .…”
Section: Memory Cd4 T‐cells Are Found Throughout the Bodymentioning
confidence: 73%
“…In the mouse model of Listeria monocytogenes infection, CXCR5 + PD1 2 CD4 + T cells were found to be the subset of central memory precursors that formed T FH more efficiently than Th1 upon boosting (60). In another study, LCMV-derived 3K peptide plus LPS immunization generated CXCR5 + endogenous CD4 + memory T cells that accelerated the kinetics (expansion/ isotype switching) of cognate naive B cell responses in a subsequent boost with 3K-OVA (61). In this study, we observed higher expression of CXCR5 and PD1 on gD-specific memory cells generated through Clec9A targeting, suggesting formation of T FH memory.…”
Section: Cd8mentioning
confidence: 97%
“…A nalyses of the mechanisms underlying memory CD4 + T-cellmediated protection have focused largely on their earlier provision of help as compared with naive cells (1), although it also is appreciated that highly activated secondary CD4 + T-cell (hereafter, 2°) effectors develop after the re-expansion of memory populations (2). Studies also suggest that optimal protection provided by T helper type 1 (T H 1)-like memory CD4 + T cells correlates with the capacity to produce multiple cytokines, including IFN-γ, TNF, and IL-2, rather than IFN-γ alone (3).…”
Section: Cytokines | Viral Infection | Immune Regulationmentioning
confidence: 99%